Migrant opportunity and the educational attainment of youth in rural China - Alan de Brauw; John Giles (Institute for the Study of Labor (IZA), 2006)
In this paper, we investigate how reductions of barriers to migration affect the decision of middle school graduates to attend high school in rural China. Change in the cost of migration is identified using exogenous variation across counties in the timing of national identity card distribution, which made it easier for rural migrants to register as temporary residents in urban destinations. We show that timing of ID card distribution is unrelated to local rainfall shocks affecting demand for migration, and not related to proxies reflecting time-varying changes in village policy or administrative capacity. We find a robust negative relationship between migrant opportunity and high school enrollment. The mechanisms behind the negative relationship are suggested by observed increases in subsequent local and migrant non-agricultural employment of high school age young adults as the size of the current village migrant network increases.
Keywords: 330; Bildungsverhalten; Bildungsabschluss; Studium; Jugendliche; Landbevölkerung; Binnenwanderung; China